Comparison of comorbidities among severe and non‐severe COVID‐19 patients in Asian versus non‐Asian populations: A systematic review and meta‐analysis - Anju Puri; Lin He; Mohan Giri; Chengfei Wu; Qinghua Zhao (Wiley, 2022)
Abstract Objectives This study aimed to evaluate the comorbidities among severe and non‐severe COVID‐19 patients in Asian versus non‐Asian populations. Design Systemic review and Meta‐analysis. Methods A systematic literature search was conducted using PubMed, Embase, Scopus and the web of science Database up to 24 March 2021. Odds ratios were calculated using a random‐effects model. Results We identified 66 studies including 39 Asian and 27 non‐Asian studies. This study demonstrated that the proportion of hypertension was significantly higher in severe group than in non‐severe group for Asian (OR = 2.46) and non‐Asian (OR = 1.60, 95% CI: 1.37-1.86, I2 = 84%; p < .00001) patients. Similarly, the proportion of diabetes, cardiovascular disease and chronic kidney disease was significantly higher in severe group than in non‐severe group for both Asian and non‐Asian studies. We found no statistically significant difference between the severe versus non‐severe group for cancer (OR = 1.26) and chronic obstructive pulmonary disease (OR = 1.32) among non‐Asian patients.